Studying the plasma‐assisted polymerization at atmospheric pressure in Ar/TEOS by active laser diagnostics. Issue 2 (17th September 2020) - Barletta, Federica; Britun, Nikolay; Leys, Christophe; Gherardi, Matteo; Snyders, Rony; Nikiforov, Anton
Abstract: The key processes in an atmospheric‐pressure plasma jet containing Ar and tetraethyl orthosilicate (TEOS) are studied by means of two‐dimensional imaging of the important discharge radicals: OH, CH, and atomic O. The kinetics of the species generation is investigated by laser‐induced fluorescence spectroscopy. The work is focused on the behavior of the ground‐state radicals' density as a function of the applied voltage and of the Ar/TEOS mixing ratio. First insights on the physicochemical mechanisms of precursor fragmentation are provided. The influence of precursor admixture and precursor fragmentation on the OH, CH radicals, and atomic oxygen kinetics is revealed. The dominant role of gas‐phase oxidation processes in CH radical formation and polymerization is discussed and analyzed. Abstract : Atmospheric‐pressure plasma jets are used for deposition of high‐quality organosilicon films. Despite the fact that deposition processes have been extensively investigated, the gas‐phase mechanisms are still far from being understood. Trying to address this gap of knowledge, this study is focused on the influence of precursor admixture on the kinetics of OH, CH, and O species formation. For the first time, both the production and recombination mechanisms for the dominant OH, CH, and O species during precursor defragmentation are identified.